The Role of Artificial Intelligence in Achieving the UN Sustainable Development Goals (SDGs) in Low Income Nations - Tarashtwal, Omid; Hakimi, Musawer; Naderi, Zuhoruddin (Universitas Pendidikan Nasional, 2025)
Artificial Intelligence has been increasingly regarded as a transformative tool to pursue the United Nations' Sustainable Development Goals, especially in low income nations plagued by infrastructural, financial, and human resource constraints that hinder sustainable development. This paper analyzes the role of AI for economic development, social inclusion, environmental sustainability, and governance by highlighting pathways, synergies, and enabling technologies. We carried out a systematic literature review based on peer reviewed journal articles published between 2020 and 2025. We searched in IEEE Xplore, Emerald Insight, MDPI, ScienceDirect, and SpringerLink databases. In total, 30 articles that were relevant to the topic, were of sufficiently high methodological quality, and were applicable to this study were included in the review. Data were extracted on the use of AI, targeted SDGs, geographic location, and key findings. Bibliometric analyses and various approaches to thematic synthesis were used to better understand research trends, keyword cooccurrence, cross SDG synergies, and newly identified challenges. Results indicate that AI improves poverty reduction, financial inclusion, optimization of the workforce, and industrial innovation; improves education, gender equality, and social equity; climate monitoring, resource management, and urban sustainability; and governance and effective partnership with regards to transparency and informed decision making. Challenges pertain to infrastructure deficits, capacity gaps, and ethical considerations. Advice for policy development, capacity building, and responsible AI deployment underpin the need for context sensitive approaches. Artificial Intelligence arises as a key enabler of integrated, scalable, and sustainable development in low income countries.